Una apuesta al tiempo y otra en juego : el sistema de pensiones y la agenda para la salud - Leal F., Gustavo; Martínez Salgado, Carolina (El Colegio de México A.C., 2000)
This text posits an interpretation of the first stages of the reform of the Mexican health and social security systems currently underway, analyzing it from a public policy perspective. It describes the general features of the context in which it emerged and characterizes the decision-making process that culminated in the modification of the Law of the Mexican Social Security Institute in 1995 and its implementation in 1997. It explores the progress achieved in the first stages of the new pensions system and points out the principal challenges faced by the second stage, involving health, still under debate at the ti- me of writing (July 1999).